Board Game Design as a Means to Educate Indonesian Novice Voters about Participating in an Elections - Ignatius Hendy Prayogo; Daniel Kurniawan Salamoon; Bing Bedjo Tanudjaja (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Apathetic about elections in Indonesia is one of few topics that are often discussed whenever the elections period is being held. With generation z attain 27. 94 percent of the total population of Indonesia, it is important that the majority of the Indonesian citizens participate and use their right to vote wisely with a mindset that cares about the nation’s future. This board game is created as a means to educate Indonesian novice voters about taking part in an election so that they are more inclined to participate and use their right of voting. Using board games as the medium makes learning more fun and conveys the message more easily.